Involvement of mediators of ros-dependent apoptosis in the contact-dependent cell death of human neutrophils induced by entamoeba histolytica trophozoites - Dingayan, Leonardo P. (Institute of Biology, College of Science, University of the Philippines Diliman, 2009)
Apoptosis in neutrophils follows a non-classical program in which redoxsensitive mediators of the caspase-dependent cascade are suppressed by the increment in the molar concentration of ROS in the cell. This "oxidative burst" is catalyzed by the NADPH Oxidase, a membrane-bound complex enzyme that assembles upon the activation of neutrophils through contact with microorganisms or with death-inducing factors. A number of reports have also evinced that certain parasitic protozoans are capable of inducing cell death by apoptosis, but reports differ on whether the pathway goes through the classical caspase-dependent cascade or through non-classical ROS-dependent routes. This study was conducted to gather clues on which pathway could be implemented in the apoptosis of neutrophils during cell to cell contact with the trophozoites of E. histlytica.f